Comparing the Influence on Non-Persuasive and Persuasive Visual on a Website and Their Impact on Users Behavioural Intention - Ibrahim, Nurulhuda; Shiratuddin, Mohd Fairuz; Wai Wong, Kok (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Research related to first impression formation has highlighted the importance of visual appeal in influencing favourable attitude towards a website. It is proposed that users are actually drawn to specific characteristics or aspects of visual design of a website, and tend to disregard other features. Therefore, this study aims to investigate which visual design strongly appeals to the users by comparing the impact of common visuals with persuasive visuals. The principles of social influence are proposed as added value to the persuasiveness of the web visuals. An experimental study is conducted and the PLS-SEM method is employed to analyse the obtained data. The result of the exploratory and confirmatory analyses demonstrated that the structural model displays better quality when tested with persuasive data sample compared to non-persuasive data sample. Thus, it is concluded that persuasive visual helps to better explain the relationship between users' attitude and intention. This means that exposure to persuasive visuals brings about consistent favourable perception to the web design.